2020
DOI: 10.1021/acsomega.0c02896
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol Effect on 2,3,7,8-Tetrachlorodibenzo-p-dioxin-Treated Japanese Quails in Terms of Serum Lipids, Liver Enzymes, Estradiol, and Thyroid Hormones

Abstract: Dioxins are compounds classified as persistent organic pollutants, from which 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) is the most toxic to living organisms. TCDD is considered a carcinogen and has proinflammatory influence on animals and humans, promoting free radicals’ formation, and binding with the aryl hydrocarbon receptor (AhR) leads to expression of cytochrome p-450 genes that in turn predisposes to mutations. Natural flavonoids, in this case xanthohumol (XN), have been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that when high doses of tocopherol are used in dioxin-contaminated animals, there is a decline in the concentration of diagnostic markers of inflammation and in the results of liver function tests [ 9 , 10 , 18 , 19 ]. In addition, it was found that acetylsalicylic acid (ASA) significantly reduces the amount of TCDD binding to cytosolic AhR, as well as potentially blocking the signal transduction initiated by exposure to the dioxin [ 11 , 20 , 21 , 22 ]. Studies in type 1-like diabetic rats have indicated that the combination of acetylsalicylic acid and α-tocopherol leads to beneficial changes that could help to protect tissues from thrombotic and ischemic phenomena [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that when high doses of tocopherol are used in dioxin-contaminated animals, there is a decline in the concentration of diagnostic markers of inflammation and in the results of liver function tests [ 9 , 10 , 18 , 19 ]. In addition, it was found that acetylsalicylic acid (ASA) significantly reduces the amount of TCDD binding to cytosolic AhR, as well as potentially blocking the signal transduction initiated by exposure to the dioxin [ 11 , 20 , 21 , 22 ]. Studies in type 1-like diabetic rats have indicated that the combination of acetylsalicylic acid and α-tocopherol leads to beneficial changes that could help to protect tissues from thrombotic and ischemic phenomena [ 23 ].…”
Section: Introductionmentioning
confidence: 99%